Chapter 5 From inner core to outer periphery Supply and demand for European (differentiated) integration - Radunz, Alexander (Taylor & Francis, 2024)
In this chapter the authors take up a journey through the map of European differentiated integration. Following the metaphor of the hemispheres, the cases selected comprise of the inner-core representative that is Germany, the outer-core represented by Poland, the inner periphery - Switzerland, and the outer-periphery that is UK, after the Brexit. Each and every state is analyzed through the supply and demand dimension, which allows for a better understanding of the political parties positioning, as well as citizens' attitudes towards European (differentiated) integration.